Alternative Splicing of the Basic Helix–Loop–Helix Transcription Factor Gene CmbHLH2 Affects Anthocyanin Biosynthesis in Ray Florets of Chrysanthemum (Chrysanthemum morifolium) - Lim, Sun-Hyung; Kim, Da-Hye; Jung, Jae-A.; Lee, Jong-Yeol (Frontiers in Plant Science, 2021)
Chrysanthemum is an important ornamental crop worldwide. Some white-flowered chrysanthemum cultivars produce red ray florets under natural cultivation conditions, but little is known about how this occurs. To explore the underlying mechanism, we compared the expression of anthocyanin biosynthetic and transcription factor genes between white ray florets and those that turned red based on cultivation conditions. Significant differences in the expression of CmbHLH2 were detected between the florets of different colors. CmbHLH2 generated two alternatively spliced transcripts, designated CmbHLH2Full and CmbHLH2Short. Compared to CmbHLH2Full, CmbHLH2Short encoded a truncated protein with only a partial MYB-interaction region and no other domains normally present in the full-length protein. Unlike the full-length form, the splicing variant protein CmbHLH2Short localized to the cytoplasm as well as the nucleus and lacked the ability to interact with CmMYB6. Additionally, CmbHLH2Short failed to activate anthocyanin biosynthetic genes and induce pigment accumulation in transiently transfected tobacco leaves, whereas CmbHLH2Full promoted both processes when simultaneously expressed with CmMYB6. Co-expressing CmbHLH2Full and CmMYB6 also enhanced the promoter activities of CmCHS and CmDFR. Notably, the Arabidopsis tt8-1 mutant, which lacks red pigmentation in the leaves and seeds, could be complemented by heterologous expression of CmbHLH2Full, which restored red pigmentation and resulted in high anthocyanin and proanthocyanidin contents in the leaves and seeds, respectively, whereas expression of CmbHLH2Short did not. Together, these results indicate that CmbHLH2 and CmMYB6 interaction plays a key role in the anthocyanin pigmentation changes of ray florets in chrysanthemum. Our findings highlight alternative splicing as a potential approach to modulate anthocyanin biosynthesis in specific tissues.